2017
DOI: 10.1186/s12862-017-1014-z
|View full text |Cite
|
Sign up to set email alerts
|

Going deeper in the automated identification of Herbarium specimens

Abstract: BackgroundHundreds of herbarium collections have accumulated a valuable heritage and knowledge of plants over several centuries. Recent initiatives started ambitious preservation plans to digitize this information and make it available to botanists and the general public through web portals. However, thousands of sheets are still unidentified at the species level while numerous sheets should be reviewed and updated following more recent taxonomic knowledge. These annotations and revisions require an unrealisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
148
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 196 publications
(151 citation statements)
references
References 27 publications
0
148
0
3
Order By: Relevance
“…Carranza‐Rojas et al. (, ) reported the first attempts to use deep learning to tackle the difficult task of identifying species in large natural history collections and showed that convolutional neural networks trained on thousands of digitized herbarium sheets are able to learn highly discriminative patterns from pressed and dried specimens. These results are very promising for extracting a broad range of other expert annotations in a fully automated way.…”
mentioning
confidence: 99%
“…Carranza‐Rojas et al. (, ) reported the first attempts to use deep learning to tackle the difficult task of identifying species in large natural history collections and showed that convolutional neural networks trained on thousands of digitized herbarium sheets are able to learn highly discriminative patterns from pressed and dried specimens. These results are very promising for extracting a broad range of other expert annotations in a fully automated way.…”
mentioning
confidence: 99%
“…As a first publication in this direction, Carranza‐Rojas, Goeau, Bonnet, Mata‐Montero, and Joly () apply deep learning methods to large herbarium image datasets. In total, more than 260,000 scans of herbarium sheets representing more than 1,204 species were analysed.…”
Section: Recent Research Studies Using Deep Learning For Species Idenmentioning
confidence: 99%
“…Recent research show that deep learning technique successfully detect plant disease or correctly classify the plant specimens in herbarium (Mohanty et al, 2016;Ramcharan et al, 2017;Carranza-Rojas et al, 2017). Deep learning is also a promising technology in the field of remote sensing because it has a natural ability to effectively encode spectral and spatial information (Yue et al, 2015;Nogueira et al, 2017), but application is not All rights reserved.…”
Section: Introductionmentioning
confidence: 99%